OPPORTUNITIES FOR INCREASING THE PROFITABILITY OF BANK ASSETS - Muxtorov Dilshod; Ernazarov Nuriddin (Ecominds Press, 2025)
This scientific article presents ideas and opinions on the development of services in banks, the importance of income from deposits in this process, and ways to increase such income.
Keywords: Bank, service, finance, consumer, investment, economy, result, product.